Fiber Amplifiers for Photonic Communication and Sensing - Yu, Yi-Lin; Liaw, Shien-Kuei; Chen, Jingo (Green Photonics and Smart Photonics, 2016)
In this chapter, several types of fiber amplifier have been demonstrated and proposed, which could be used in communication and sensing, including Erbium doped fiber amplifier (EDFA), Raman fiber amplifier (RFA), hybrid fiber amplifier (EDFA+ RFA) and high power fiber amplifier. The authors also used the concept of residual pumping reused to optimize the gain efficiency of C + L band signals. This chapter proposes four kinds of fiber amplifier, EDFA, Raman fiber amplifier, hybrid fiber amplifier, and high-power fiber amplifier. It proposes a bidirectional EDFA and a bidirectional hybrid fiber amplifier. The chapter employs the concept of residual pumping power reuse to optimize the gain efficiency of C + L band signals. It proposes a new architecture of RFA based on signal and pump double-pass the gain medium and cascaded FBGs to increase the pumping efficiency. In a RFA-based WDM system, it is difficult to use only one segment of DCF for compensating WDM channels in the whole C and/or L-band. It is attributed to the mismatch of dispersion slope of the DCF and the standard fiber, that is, SMF. The chapter uses Er/Yb codoped fiber as the gain medium of high power fiber amplifier.